2011
DOI: 10.1007/s10854-011-0525-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct-on-barrier copper electroplating on ruthenium from the ionic liquid 1-ethyl-3-methylimidazolium dicyanamide

Abstract: The ''direct-on-barrier'' electroplating of copper on ruthenium from a 1 mol dm -3 solution of CuCl in the ionic liquid 1-ethyl-3-methylimidazolium dicyanamide, [C 2 mim][N(CN) 2 ], is reported. Continuous layers of copper with a preferential Cu(111) orientation were obtained from this electrolyte. The copper coatings were investigated by top view scanning electron microscopy (SEM), X-ray diffraction (XRD), and focused ion beam transmission electron microscopy (FIB-TEM). The nucleation density was both theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Ruthenium (Ru), a novel barrier layer material, the application of which is quite promising in the new generation of integrated circuit. 1 A thin film of Ru (several nanometers) often lies between Cu and the low-k dielectric material, preventing interfacial diffusion between Cu and the substrate. 2,3 Since the polishing solutions used in the CMP process are corrosive and abrasive, the galvanic corrosion at the Cu/Ru interface is unavoidable and detrimental.…”
mentioning
confidence: 99%
“…Ruthenium (Ru), a novel barrier layer material, the application of which is quite promising in the new generation of integrated circuit. 1 A thin film of Ru (several nanometers) often lies between Cu and the low-k dielectric material, preventing interfacial diffusion between Cu and the substrate. 2,3 Since the polishing solutions used in the CMP process are corrosive and abrasive, the galvanic corrosion at the Cu/Ru interface is unavoidable and detrimental.…”
mentioning
confidence: 99%
“…However, at a P-ratio of 6 with a high concentration of Cu ions, the overpotential was relatively low due to the high conductivity of the solution. It was reported that the Cu nucleation density on the barrier layer decreases as the overpotential decreases [11]. When the Cu nucleation density was low, the adhesion of the Cu plated on the Ti surface as a barrier layer could be poor [12].…”
Section: Effects Of the P-ratio And Current Densitymentioning
confidence: 99%
“…Copper electrodeposition has good agreement with HDI microvias metallization due to its void-free filling in the features, minimal topography of the final copper surface, and controllable impurity incorporation in the plated copper film [3][4][5].…”
mentioning
confidence: 90%